The Effect of Solar Chimney Dimensions on its Performance in Nasiriya City Weather Conditions - M. Hannun, Rafid; Togun, Hussein; H. Khalaf, Mohammed; M. Abed, Tariq (International Journal of Engineering and Technology, 2018)
In this study, a numerical study was carried out on the effect of the solar chimney dimensions on its performance. Five different models of solar chimney were studied in terms of the diameter of the solar collector, the height of the air intake entrance of the collector and the height of the solar chimney. The five models were compared with others according to the conditions surrounding the solar chimney. The study showed that the increase in the dimensions of the solar chimney increases the utilized energy and the external air velocity is inversely proportional to the performance of the solar chimney due to increasing the thermal losses from the collector. The results showed also that increasing the temperature of the ambient air and the solar radiation increases the performance and productivity of the solar chimney. The analytical results of this paper were compared with previous literature studies and showed a great convergence between them.Â Â